Kajian pengaruh perubahan penutup lahan terhadap kenaikan suhu permukaan di Kota Yogyakarta - Nuraini Sekarsih, Fitria; Khasanah, Uswatun; Gangga, Panji Setya; Saputra, Ridho Abdhe (Jurnal Media Informatika, 2024)
Land cover in Yogyakarta City has changed during 2013-2023. This change is predicted to be the cause of surface temperature increasing in Yogyakarta City. Analysis of the influence of these factors on surface temperature was carried out using Landsat 8 imagery with 4 stages, 1) downloading and making corrections of images; 2) processing the image to obtain the surface temperature value; 3) processing the image to obtain land cover, built-up land, and humidity index values; and 4) making sampling to analyze the relationship between surface temperature and land cover. As a result, there was 0.380 C surface temperature increasing during 2013-2023. This is in line with changes in land cover in Yogyakarta City where the vegetation index has decreased, while the built-up land index has increased. In 2013, land cover was the dominant factor in surface temperature in Yogyakarta City, and it affected of 91.16%. Meanwhile, in 2023 the influence of land cover was only 49.42%. The pandemic era can be a reference for the influence of pollutants on surface temperatures. The results show that there was a significant decrease in temperature during the pandemic become 30.140C. This data is supported by the increase number in motorized vehicles in the City of Yogyakarta. The increase number of motorized vehicle is about 124% in the past decade.